LA CONCIENCIA FONOLÓGICA PARA EL DESARROLLO DE LA LECTURA EN EL SEGUNDO AÑO DE EDUCACIÓN GENERAL BÁSICA DE LA UNIDAD EDUCATIVA LICEO IBEROAMERICANO, PERÍODO 2018 - 2019 - Sula Llamuca, Mónica Fernanda (2019)
The main objective of this research project was the development of awareness to improve the reading of children in the second year of Basic General Education of the Liceo Iberoamericano Educational Unit period 2018-2019. The study variables are described through the collection of information from books, magazines, websites, among others; meanwhile, the methodology had a qualitative approach and was framed in the field of educational sciences and was configured as a humanistic study. The design was not experimental because the study variables were not manipulated. The type of research was diagnostic - exploratory, that the investigation is based on a situational analysis of the phenomenon of the problem and the application of activities for the development of phonological awareness. The population was conformed by 19 students of Second Degree of Basic of the Educational Unit "Liceo Iberoamericano"; therefore, being a small population it was not necessary to carry out sampling. The applied instruments: observation cards and check cards recognized the work experience that we had as main results, reducing some difficulties: reading broken by the little differentiation of the sounds of the syllables that respond, similar calligraphic features and disorder of the letters and syllables.